Influence of Van der Waals Interactions on the Solvation Energies of Adsorbates at Pt‐Based Electrocatalysts. Issue 22 (19th August 2019) - Granda‐Marulanda, Laura P.; Builes, Santiago; Koper, Marc T. M.; Calle‐Vallejo, Federico
Abstract: Solvation can significantly modify the adsorption energy of species at surfaces, thereby influencing the performance of electrocatalysts and liquid‐phase catalysts. Thus, it is important to understand adsorbate solvation at the nanoscale. Here we evaluate the effect of van der Waals (vdW) interactions described by different approaches on the solvation energy of *OH adsorbed on near‐surface alloys (NSAs) of Pt. Our results show that the studied functionals can be divided into two groups, each with rather similar average *OH solvation energies: (1) PBE and PW91; and (2) vdW functionals, RPBE, PBE‐D3 and RPBE‐D3. On average, *OH solvation energies are less negative by ∼0.14 eV in group (2) compared to (1), and the values for a given alloy can be extrapolated from one functional to another within the same group. Depending on the desired level of accuracy, these concrete observations and our tabulated values can be used to rapidly incorporate solvation into models for electrocatalysis and liquid‐phase catalysis. Abstract : Water solvation modifies the adsorption energies of *OH, and therefore, also the oxygen‐reduction activity of Pt electrocatalysts. The authors show that *OH solvation on Pt(111) near‐surface alloys depends on the exchange‐correlation functional used and whether long‐range interactions are included or not. They divide the functionals into two groups so that extrapolating *OH solvation energies within a given group is safe. However, extrapolations between different groups should be avoided if accurate activity predictions are to be made.